A strategic management plan College of Science and Mathematics University of the Philippines Mindanao - Tagubase, Jackie Lou J. (School of Management, University of the Philippines Mindanao, 2009)
The College of Science and Mathematics (CSM) is one of the three degree granting units of the University of the Philippines Mindanao. It is further clustered into three departments: Food Science (FSC), Biological Sciences and Environmental Studies (BSES), and the Math, Physics and Computer Science (MPCS). The DFSC administers the BS Food Technology program of the college, DBSES offers the BS Biology program, and the DMPCS administers the BS Applied Mathematics and BS Computer Science courses. The College primarily exists towards advocacy of scientific knowledge in policy making and development programs, nurturance of environmental and life sciences, pioneering of utilization of information technology for agri-systems, defense of academic freedom in Mindanao, and agri-system innovation. To identify the strategic direction that CSM intends to take in the next five years, the strategic management model presented by David (2004) was adapted. Personal communication, interviews and perusal of official documents were made to provide an analysis of the internal factors that drive the organization's processes. External factors that may affect the organization were also scanned and analyzed. The proposed strategy includes building identity and visibility of the College among its target market to promote the programs and services offered by the College and facilitate the creation of its self- generating funds for the improvement and sustainability of it processes. The research activities of the college must be redirected to vertically-integrated activities to strengthen external linkages. Further, empowering its human resource to improve their morale and develop programs for more efficient and effective processes of the college are proposed to support the primary strategy. The overall strategy involves several long-running programs covering the four functional areas of the organization.